Obligation to leave the premises occupied jointly with the victim as a probation measure (Ius Novum, 2025)
The subject of the article is the obligation to leave the premises occupied jointly with the aggrieved party, imposed on the accused person as a probation measure. The considerations include the evolution of this obligation, its legal nature, purpose, essence, grounds, mode of adjudication, timing, manner of execution and the effects of its violation. The aim of the article is to analyse the probation measure of the perpetrator’s obligation to leave the premises occupied jointly with the aggrieved party and to indicate the function fulfilled by this measure. The research thesis is that the obligation to leave residential premises occupied jointly with the aggrieved party as a probation measure serves mainly to protect the aggrieved, and affects the convicted person to a lesser extent. The research hypothesis is the assumption that this obligation is generally regulated correctly and requires some small normative amendments. The theoretical-legal method is used in the article, as it focuses on the analysis of theoretical aspects of this order and its normative analysis in relation to the views of representatives of the doctrine.